'Zróbmy coś - 'dajcie coś'. Dwie konceptualizacje projektów rozwojowych - Ryszard Vorbrich (Etnografia Polska, 2013)
The paper discusses the results of a research project entitled Passive beneficiary versus local partner of development projects. Conceptualisation and adaptive strategies concerning development cooperation of African local communities (Comparative study). The research was conducted in Cameroon, Mali and Morocco in 2011-2013. Author's experiences from previous research conducted in Africa were also used to write this paper. The Author, by referring to a postmodern development critics, analyses two models of development project conceptualisation. He labels them with contrary phrases: let's do something' and 'give us something'. The analysis gains from the theory of linguistic games by Ludwig Wittgenstein and from the concept of two scripts of a project (public and secret ones). The basic thesis of the paper says that applying the given model depends on the place in a chain of presence in the project. The first model is associated by the Author with project initiators (so called 'developpers'), while the second with the beneficiaries (so called 'being developed'). Existence of these two models of development projects conceptualisation is connected with selective attitudes towards what the particular development project can offer (including its technological package). Selecting one of these two models has essential meaning for projects effectiveness.